Three‐phase hollow fiber liquid‐phase microextraction combined with HPLC for determination of three trace acidic plant growth regulators in Anoectochilus roxburghii (Wall.) Lindl. Issue 14 (20th May 2020) - Hong, Ruixia; Wu, Pingping; Lin, Jin; Huang, Liying; Yang, Lijuan; Wu, Youjia; Yao, Hong
Abstract: The analysis of plant growth regulators presents a challenge due to their trace quantities and complex matrices. A novel, simple, and effective analytical method for the determination of three trace acidic plant growth regulators in Anoectochilus roxburghii (Wall.) Lindl was developed to address this issue. Three‐phase hollow fiber liquid‐phase microextraction combined with high‐performance liquid chromatography was applied for the enrichment, purification, and determination of three acidic plant growth regulators, namely, indole‐3‐acetic‐acid, indole‐3‐butyric‐acid, and (+)‐abscisic acid. The factors affecting extraction performance, including extractant species, pH of donor and acceptor phases, salt addition dosage, extraction time, temperature, and stirring rate, were investigated and optimized. Under optimum conditions, the proposed method provided good linearity ( R 2, 0.9994–0.9999), low limit of detection (0.038–0.12 ng/mL), and acceptable relative recoveries (56.7–117.6%). The enrichment factors were between 153 and 328. The developed method was successfully applied to the enrichment and determination of plant growth regulators in Anoectochilus roxburghii (Wall.) Lindl and exhibited increased purification capacity, higher sensitivity, and decreased organic solvent consumption compared with conventional sample preparation methods. This method may provide a testing platform for the monitoring of plant growth regulator residues, ensuring the safe and effective use of traditional Chinese medicine.